An Oblivious Transfer Protocol with Log-Squared Communication - Lipmaa, Helger (Information Security, 2005)
We propose a one-round 1-out-of-n computationally-private information retrieval protocol for ℓ-bit strings with low-degree polylogarithmic receiver-computation, linear sender-computation and communication Θ(klog2n+ℓlogn), where k is a possibly non-constant security parameter. The new protocol is receiver-private if the underlying length-flexible additively homomorphic public-key cryptosystem is IND-CPA secure. It can be transformed to a one-round computationally receiver-private and information-theoretically sender-private 1-out-of-n oblivious-transfer protocol for ℓ-bit strings, that has the same asymptotic communication and is private in the standard complexity-theoretic model.